(3GdYeOI aj GdCMcGe GdefbhdI Yf NjQ GdCfGes - (3GdMGaX Jbj GdOjf CHj eMeO YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ GdLeGYjdj GdebOSj GdLeGYjdj GdMfHdj,J (B600 (3g` s ((3eMeO Hf eMeO Hf eMeO Hf SeGc GdYGedi s)
(3ChdgG (B:s
(3CeG HYO aEf HYV ENhGfi SCdfi GNJUGQ hLedI ai CMGOjK GdCMcGe , aeG EJab Ydjg GdEeGeGf CHh YHO Gddg eMeO Hf ESeGYjd Hf EHQGgje , hSde Hf GdMLGL aCLHJg EdiSDGdg QLGA GdefaYI Hg s
(3BNQgG (B:s
(3de jcf dg eGd ZjQg , aHGYg HKeGf eGFI OQge , Ke CQSd Kefg Edjg Je cJGH GdYeOI s
(3GdfSNI HgG MhGTs
(3bGHdgG GdfGS Ydi CUd UMjM ai faS GdSfIs
(3Ydi GdfSNI bQGAGJ CNQi hELGRGJ HgG hYQhV SfhGJ (B759 (3, (B762(3, (B764(3, (B793 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs